Upaya Meningkatkan Minat dan Hasil Belajar Matematika Siswa Melalui Model Pembelajaran Berbasis Masalah - Haris Munandar; Nurhasanah Siregar (ALFIHRIS : Jurnal Inspirasi Pendidikan, 2024)
This research aims to determine the problem-based learning model in increasing students' interest and learning outcomes in mathematics. This type of research is Classroom Action Research (PTK) with a model from Kemmis and McTaggart. The subjects in this research were 30 students of SMP Negeri 1 Secanggang. The object of this research is learning by applying a problem-based learning model to increase students' interest and learning outcomes in mathematics. The research results showed that students' interest in learning mathematics in cycle I was 73.7% (classified as moderate) which then increased in cycle II to 91.3% (classified as very high). The increase in N-Gain in students' interest in learning mathematics from Cycle I to Cycle II was 0.66 and was included in the medium category. Meanwhile, for students' mathematics learning outcomes during cycle I, 23 students achieved the Minimum Completeness Criteria (MCC) with a classical completeness percentage of 76.67%. The N-Gain obtained from students' mathematics learning results from the pre-test and post-test assessments in cycle I was 0.60 and was included in the medium category. Then the students' mathematics learning results in cycle II obtained 26 students who achieved the MCC with a classical completion percentage of 86.67%. The N-Gain obtained from students' mathematics learning results from the pre-test and post-test assessments in cycle II was 0.65 and was included in the medium category. This confirms that the problem-based learning model can increase student interest and learning outcomes in mathematics lessons in Class VII-5 of SMP Negeri 1 Secanggang.